Representing the national landscape in Irish Romanticism - Wright, Julia M. (Syracuse University Press, 2014)
Ireland is a country which has come to be defined in part by an ideology which conflates nationalism with the land. From the Irish Revival's celebration of the Irish peasant farmer as the ideal Irishman to the fierce history of land claim battles between the Irish and their colonizers, notions of the land have become particularly bound up with conceptions of what Ireland is and what it is to be Irish. In this book, Wright considers this fraught relationship between land and national identity in Irish literature. In doing so, she presents a new vision of the Irish national landscape as one that is vitally connected to larger geographical spheres. By exploring issues of globalization, international radicalism, trade routes, and the export of natural resources, Wright is at the cutting edge of modern global scholarly trends and concerns. In considering texts from the Romantic era such as Leslie's Killarney, Edgeworth's "Limerick Gloves," and Moore's Irish melodies, Wright undercuts the nationalist myth of a "people of the soil" using the very texts which helped to construct this myth. Reigniting the field of Irish Romanticism, Wright presents original readings which call into question politically motivated mythologies while energizing nationalist conceptions that reflect transnational networks and mobility.
Keywords: English literature -- Irish authors -- History and criticism.; English literature -- 19th century -- History and criticism.; National characteristics, Irish, in literature.; Romanticism -- Ireland.; Littérature anglaise -- Auteurs irlandais -- Histoire et critique.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Romantisme -- Irlande.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English literature; English literature -- Irish authors; National characteristics, Irish, in literature; Romanticism; Ireland; 1800-1899; Criticism, interpretation, etc.